Basic Ways and Critical Issues to Open Bank Accounts - Namozov Bekjon (Genius Journals, 2023)
The article describes the main ways of opening bank accounts, i.e., the processes required for opening bank accounts by individuals or organizations. These processes usually involve visiting a bank branch, using online banking services, or opening an account through mobile apps. The article also presents important rules and requirements for opening bank accounts. These requirements include personal information of the person, legal information of the organization, types of payment, minimum funds, necessary documents for opening the account, etc. The article also points out the critical issues of opening bank accounts. Among these problems are high commissions offered by banks, lengthy account opening processes, account management difficulties, security issues and quality of service issues. The article analyzes the main ways and critical issues of opening bank accounts and will be useful for teachers, students and general educators.
Keywords: bank accounts,; banks and banking activity; Types of bank accounts